A new species of Gracixalus (Anura: Rhacophoridae) with a hyperextended vocal repertoire from Vietnam - Rowley, Jodi J. L.; Dau, Vinh Quang; Nguyen, Tao Thien; Cao, Trung Tien; van Nguyen, Sang (Zootaxa, 2011)
We describe a new species of small rhacophorid frog from north central Vietnam. Gracixalus quangi sp. nov. is morphologically and genetically most similar to G. gracilipes and G. supercornutus, but is distinguished from these species and all other rhacophorids in Vietnam and adjoining countries by a combination of their small size (males Gracixalus quangi sp. nov. has a non-stereotypical, hyperextended vocal repertoire, with calls highly variable in structure, duration, amplitude and frequency (dominant frequency 4.1–4.7 kHz). Like G. gracilipes and G. supercornutus, G. quangi sp. nov. deposits egg clutches in clumps on leaves overhanging shallow forest pools or puddles. The new species is known from montane evergreen forest in Pu Hoat Proposed Nature Reserve in western Nghe An Province, between 600–1,300 m elevation. Preliminary molecular (mtDNA) data recovered two strongly supported clades within frogs currently considered to belong to genus Gracixalus, with the new species nested within a monophyletic clade consisting of G. gracilipes, G. supercornutus, and G. quyeti.